Analisis Penerimaan E-Learning Selama Pembelajaran Jarak Jauh Menggunakan Unified Theory Of Acceptance and Use of Technology (UTAUT) - Rifqi Ramadhan Tussardi; Berlian Maulidya Izzati; Muhardi Saputra (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2021)
The new coronavirus disease that was first identified in Wuhan, China, is referred to as the 2019 coronavirus disease pandemic (COVID-19). The impact of this pandemic has affected various fields, one of which is education, and one of the consequences is the implementation of online teaching and learning processes. In this digital era, Telkom University is implementing CeLOE LMS as an E-Learning medium. CeLOE Learning Management System (LMS) is an online learning platform for regular and distance education study programs at Telkom University. For the application of CeLOE LMS, there has been no report that contains user acceptance of the use of CeLOE LMS that tested with an integrated model. Therefore, the solution offered by this research was to conduct an analysis to determine user acceptance of the application of the CeLOE LMS system by using the Unified Theory of Acceptance and Use of Technology (UTAUT) Model at Telkom University to produce report that can be used as a basis for further decision making by Telkom University in managing its services as the UTAUT Model attempts to clarify the intentions of students to use an information system and the usage actions of students. From this research, it was found that the CeLOE LMS has been accepted and used by Telkom University students with all hypotheses accepted, Performance Expectancy as the variable with the greatest influence, and it needs improvements related to technical infrastructure, organizational infrastructure, and socialization of CeLOE LMS due to the influence of Facilitating Conditions variable was the lowest.